Cohort profile of the GOALS study: A large‐scale research of physical activity in Dutch students. (29th April 2015) - de Groot, Renate H.M.; van Dijk, Martin L.; Kirschner, Paul A.
Abstract The GOALS study (Grootschalig Onderzoek naar Activiteiten van Limburgse Scholieren [Large‐scale Research of Activities in Dutch Students]) was set up to investigate possible associations between different forms of physical activity and inactivity with cognitive performance, academic achievement and mental well‐being. It was conducted at a secondary school in the south of the Netherlands. Data collection took place during normal school weeks from October 2011 to March 2012, and 1 year later from October 2012 to May 2013. The study was approved by the local Ethical Committee of the Open University of the Netherlands. All students in grades 7 and 9 of senior general secondary education and university preparatory education were invited to participate (n = 526). At baseline, a sample of 440 Dutch‐speaking adolescents was willing to participate (83.7%). Of these, 344 participated in the follow‐up. Physical activity was measured objectively by an ActivPal3TM accelerometer (Paltechnologies, Glasgow, UK). Cognitive performance was measured by the d2 Test of Attention and the Symbol Digit Modalities Test. Academic achievement was determined using the mean of school grades in Dutch, English and Mathematics. Several well‐validated instruments were used to determine mood/depressive symptoms, self‐esteem and goal orientation. Information on several covariates such as sex, academic year, school level, ethnicity, socio‐economic status, body mass index, pubertal status, smoking, drinking, viewing television, computer use, etc., are available.